HUBUNGAN ANTARA DURASI PENGGUNAAN SMARTPHONE DENGAN KELUHAN NYERI PERGELANGAN TANGAN PADA TIM E-SPORT MOBILE LEGEND UPN VETERAN JAKARTA - Achika Beauty Sarinah (2022)
Smartphone is a cellular phone (cell phone) that has a complete operating system. Gamers is a term for game users consisting of 51% smartphone gamers and 49% computer users. E-Sport is a sport that hones neurocognitive skills including effective hand-eye coordination in developing reaction time and fast decision making in a virtual competitive environment. Musculoskeletal complaints when operating a smartphone are caused by gripping or clamping movements strongly, extreme positions of the wrist such as ulnar deviation, posture when using a smartphone in static movements with physiological repetitive flexion and extension positions of the wrist can cause shortening of connective tissue and muscles. The purpose of this research was to determine the relationship between the duration of smartphone use and wrist pain in UPN Veterans Jakarta students. This research uses a correlational cross-sectional study approach with a total sample of 88 respondents. Data were collected to measure the duration of smartphone use are hours and wrist pain by NRS. Processing the data in this study are based on SPSS 25, the Pearson correlation coefficient was obtained with p = 0.245 (< 0.05). The conclusion of this study revealed a relationship between the duration of smartphone use and wrist pain which is positive or unidirectional.